Chimeric Antigen Receptor T-Cell Therapy Is Associated with Low Absolute Rates of Orofacial Adverse Events and Significantly Less When Compared to Hemopoietic Stem Cell Therapy - Stella O. Oyewole; Emma Butler; Sagun D. Goyal; Adepitan A. Owosho (Dentistry Journal, 2026)
Background/Objectives: Chimeric antigen receptor T-cell (CAR-T) therapy has been approved for the management of relapsed and refractory hematologic malignancies, transforming the oncologic landscape and producing durable remissions in patient populations with limited alternatives. The systemic adverse events of CAR-T are well characterized; however, the orofacial adverse events have not been well described. The objective of this study is to leverage a large, de-identified, real-world dataset to (1) estimate the prevalence of orofacial adverse events following CAR-T, (2) compare event rates with the general population, and (3) directly contrast the orofacial toxicity burden of CAR-T with that observed after hemopoietic stem cell transplant (HSCT). Methods: We performed a retrospective cohort study using de-identified electronic health record data from TriNetX. CAR-T and HSCT cohorts were identified via RxNorm and procedure codes; a non-exposed control cohort was included. Patients with prior orofacial conditions or confounding therapies were excluded. New adverse orofacial events within one year were identified by International Classification of Diseases, 10th Revision (ICD-10) codes. Cohorts were 1:1 propensity-matched by age and sex; associations were estimated as odds ratios with two-sided 95% CIs. Results: In 1142 CAR-T recipients (mean age of 62), gastroesophageal reflux disease (GERD) was most frequent (5.18%). Oral mucosal events included stomatitis in 1.52%, mucositis in 1.31%, and lichenoid reactions in 1.03%. Dysphagia occurred in 1.8% and oral candidiasis in 1.6%. Several severe oral conditions were absent. Compared with the general population (CART vs. general population): mucositis—[12/995 vs. 0/1112] (OR 28.3)—and stomatitis—[16/987 vs. 0/1119] (OR 38)—risks were significantly increased, while CAR-T patients had significant lower risks of mucosal complications than HSCT recipients in this analysis (CART vs. HSCT): mucositis—[1.21% vs. 3.72%] (OR 0.316) and stomatitis—[1.42% vs. 3.91%] (OR 0.354). Conclusions: CAR-T therapy carries a distinct and generally lower orofacial toxicity burden than HSCT, but targeted dental assessment and prospective surveillance remain important to optimize supportive care for cellular therapy recipients.